Influence of Construction Materials on Cut-Off Grade and Ore Reserve Determination: CaseStudy of Itakpe Deposit, CentralNigeria - Nwosu, J.I.; Nwankwoala, H.O (IJRDO-Journal of Applied Science, 2018)
The presenceconstruction materialsin an ore deposit can add value to the deposit andaffect cut -off grade.In this paper , the influence of the presence of granite and aplites onthe cut-off grade and ore reserve of Itakpe Iron ore deposit has been studied. This studywas carried out by converting the values and production costs of the construction stonesto their main ore equivalent using some mathematic al models. The study shows that byadding the value of the con struction materials to the value of the iron ore, cut -off grade ofItakpe iron ore decreases from 30%Fe to 28.16%Fe. This corresponds to an increase ofmineable orereserve from 137.25mt to 151. 34mt given the operating economicparameters.